Mineral Status of Lactating Jaffarabadi Buffaloes in Their Home Tract: A Field Study - Naliyapara, Hardik B.; Savsani, Harish H.; Chavda, Mitesh R.; Chavda, Jignesh A.; Chaudhry, Girish M.; Ribadiya, Nilay K.; Karangiya, Vijay K. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Deficit macro and micro-minerals in the ration of lactating Jaffarabadi buffaloes adversely affects growth, milk production and reproduction efficiency. For present study, four villages from each of 5 talukas were selected at random for taking representative samples of soil, feeds, forages and blood plasma of lactating Jaffarabadi buffaloes. Within the village, help was sought from village milk producers and district animal husbandry officer for identification of 3 farmers and collection of representative samples. All the samples were processed and analysed for chemical composition as well as major macro and micro-minerals, using Microwave Plasma Atomic Emission Spectrometer (MP-AES). Ca content was high in groundnut haulms (0.95%), but maize forage (0.23%), cotton seed cake (0.16%), cotton seed (0.12%) and maize cake (0.25) were found to be below the critical level (0.30%). The P content in concentrate ingredients was high (0.38-0.68%), but low in roughages (0.07-0.20%). Green jowar (0.18%) and maize cake (0.10%) were deficient in Mg. Feeds and forages were found to be adequate in iron. Abundant level of Cu was found in all feeds and forage. Sugarcane was found deficient in all minerals, except iron, and groundnut haulms (20.70 ppm) were found to be deficient in Zn.  The blood mineral profile of the majority of lactating Jaffarabadi buffaloes was adequate. From the present study, it was apparent that soil and therefore forages cultivated in particular region were deficient in P and Zn. Same minerals were adequate in concentrate available in this area. So, to fulfil the requirement of deficient minerals there is need to feed concentrate along with area specific mineral mixture to the buffaloes.
Keywords: Feeds; Forage; Jaffarabadi buffaloes; Minerals; Soil